Determinans Sustainability Report, Leverage and Tax Avoidance on Financial Performance with CEO Narcissism as Moderation Variable - Saepulloh, Muhammad; Yanti, Yanti; Arimurti, Trias (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
Financial performance analysis is the process of critically reviewing finances which involves reviewing data, calculating, measuring and providing financial solutions. Sustainability reports, leverage, tax avoidance and CEO marcissism are among the factors that influence a company's financial performance. This study examines the impact of tax avoidance, leverage, and sustainability reports on financial performance using CEO narcissism as a moderating factor. With a population of 89 companies in the metals and minerals industry, the subjects of this study are manufacturing companies listed on the Indonesia Stock Exchange. Secondary data sources and quantitative techniques are used in this research methodology. Using SmartPLS version 3, the Partial Least Squares (PLS) approach was used in the data processing procedure. The results show that although the tax avoidance variable has no influence and the CEO narcissism variable cannot mitigate the relationship between tax avoidance and financial success, the sustainability report and leverage variables have a great influence on financial performance. This research is aimed at companies operating in the metal and mineral manufacturing industry to reveal the environmental, social and economic role of society as well as the attractiveness of external parties, namely investors.